2010
DOI: 10.1002/bies.201000066
|View full text |Cite
|
Sign up to set email alerts
|

The hidden benefits of sex: Evidence for MHC‐associated mate choice in primate societies

Abstract: Major histocompatibility complex (MHC)-associated mate choice is thought to give offspring a fitness advantage through disease resistance. Primates offer a unique opportunity to understand MHC-associated mate choice within our own zoological order, while their social diversity provides an exceptional setting to examine the genetic determinants and consequences of mate choice in animal societies. Although mate choice is constrained by social context, increasing evidence shows that MHCdependent mate choice occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 97 publications
1
56
0
Order By: Relevance
“…129 Indeed, nonhuman primate studies are necessary to fully understand the evolution of MHC-mediated mate selection in humans because they allow us to track the evolutionary trajectory of the preference and to study the selective pressures favoring the traits' emergence and maintenance. 67 Complementing similar behavioral traits, nonhuman primates share a number of genetic traits, including orthologous MHC genes, with humans. 130 Further, identical MHC allele motifs are associated with resistance to related pathogens, for example, to simian immunodeficiency virus (SIV), the predecessor of HIV.…”
Section: Human Vs Nonhuman Primate Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…129 Indeed, nonhuman primate studies are necessary to fully understand the evolution of MHC-mediated mate selection in humans because they allow us to track the evolutionary trajectory of the preference and to study the selective pressures favoring the traits' emergence and maintenance. 67 Complementing similar behavioral traits, nonhuman primates share a number of genetic traits, including orthologous MHC genes, with humans. 130 Further, identical MHC allele motifs are associated with resistance to related pathogens, for example, to simian immunodeficiency virus (SIV), the predecessor of HIV.…”
Section: Human Vs Nonhuman Primate Populationsmentioning
confidence: 99%
“…The solid line in (A) and (B) denotes nonsignificant results. Data from the recent review by Setchell and Huchard, 67 and additional studies were identified up from 2009 to January 2015 via Web of Science using the topic "MHC" or "major histocompatibility complex" and "mate choice" or "mate selection" or "mate preference" and searching within results for "primate". Abbreviation: MHC, major histocompatibility complex.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Odor-mediated MHC-disassortative mating promotes offspring heterozygosity and is evolutionarily beneficial because of heterozygote advantage in resistance to infection. MHC-disassortative mating occurs across fish, reptiles, birds, and mammals (Milinski, 2006;Penn, 2002;Roberts, 2009;Setchell & Huchard, 2010). In some socially monogamous birds and mammals (including primates), females not only choose to pair with MHC-dissimilar mates but are also more likely to engage in extra-pair copulations (evidenced by mixed paternity clutches) if their mate is relatively MHC-similar (FreemanGallant, Wheelwright, Meiklejohn, & Sollecito, 2006;Schwensow, Fietz, Dausmann, & Sommer, 2008); in so doing, they gain further genetic diversity in their offspring, with associated benefits in offspring health and survival (Foerster, Delhey, Johnsen, Lifjeld, & Kempenaers, 2003;Petrie & Kempenaers, 1998).…”
Section: Mhc-correlated Partner Preferencementioning
confidence: 99%
“…Consequently, although the Hutterites study clearly points to MHCdisassortative mating, we have to consider the possibility that the excess of dissimilarity observed at the MHC level among European American spouses from the HapMap dataset reflects a combination of pre-copulatory (mate choice) and post-copulatory processes, the latter aiming at further increasing MHC heterozygosity in the offspring [33][34][35][36][37]. This hypothesis is further supported by the observation that genes potentially involved in either prezygotic female choice or pregnancy loss displayed signatures of extreme dissimilarity among spouses in the HapMap dataset [38].…”
Section: Mhc-dependent Mate Choice May Be Restricted To Certain Humanmentioning
confidence: 99%